Differential allelic expression of IL13 and CSF2 genes associated with asthma - Burkhardt, Jana; Kirsten, Holger; Wolfram, Grit; Quente, Elfi; Ahnert, Peter (Genetics and molecular biology, 2012)
An important area of genetic research is the identification of functional mechanisms in polymorphisms associated with diseases. A highly relevant functional mechanism is the influence of polymorphisms on gene expression levels (differential allelic expression, DAE). The coding single nucleotide polymorphisms (SNPs) CSF2(rs25882) and IL13(rs20541) have been associated with asthma. In this work, we investigated whether the mRNA expression levels of CSF2 or IL13 were correlated with these SNPs. Samples were analyzed by mass spectrometry-based quantification of gene expression. Both SNPs influenced gene expression levels (CSF2(rs25882): p(overall) = 0.008 and p(DAE samples) = 0.00006; IL13(rs20541): p(overall) = 0.059 and p(DAE samples) = 0.036). For CSF2, the expression level was increased by 27.4% (95% CI: 18.5%-35.4%) in samples with significant DAE in the presence of one copy of risk variant CSF2(rs25882-T). The average expression level of IL13 was increased by 29.8% (95% CI: 3.1%-63.4%) in samples with significant DAE in the presence of one copy of risk variant IL13(rs20541-A). Enhanced expression of CSF2 could stimulate macrophages and neutrophils during inflammation and may be related to the etiology of asthma. For IL-13, higher expression could enhance the functional activity of the asthma-associated isoform. Overall, the analysis of DAE provides an efficient approach for identifying possible functional mechanisms that link disease-associated variants with altered gene expression levels.